2010
DOI: 10.1093/cid/ciq019
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a Monovalent 2009 Influenza A (H1N1) Vaccine in an Immunocompromised Population: A Prospective Study Comparing HIV-Infected Adults with HIV-Uninfected Adults

Abstract: Despite high CD4 cell counts and receipt of antiretroviral medications, HIV-infected adults generated significantly poorer antibody responses, compared with HIV-uninfected persons. Future studies evaluating a 2-dose series or more-immunogenic influenza A (H1N1) vaccines among HIV-infected adults are needed (ClinicalTrials.gov NCT00996970).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 39 publications
(53 reference statements)
7
64
5
Order By: Relevance
“…Studies in patients infected with HIV-1 have shown that anti-influenza-specific antibody responses correlated with the CD4 T cell count 34 . Indeed, HIV-1 infected patients generated poorer responses to monovalent influenza A H1N1/2009 vaccine compared to healthy subjects 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients infected with HIV-1 have shown that anti-influenza-specific antibody responses correlated with the CD4 T cell count 34 . Indeed, HIV-1 infected patients generated poorer responses to monovalent influenza A H1N1/2009 vaccine compared to healthy subjects 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies on the efficacy of MF59-adjuvanted 2009 pandemic A/H1N1 influenza vaccine (A/H1N1/Cal/09) suggested a lower rate of influenza seroconversion in HIV-infected individuals (36.4-69%) as compared with healthy donors ( > 79%), [18][19][20] even in patients with high CD4 T cell counts. 21 In contrast, other studies reported a good antibody response in successfully HAART-treated HIV patients. 22,23 However, all these studies addressed the humoral response only, and no information about the ability of pandemic vaccine to elicit a strain-specific and cross-reactive T cell response is available in HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 90%
“…7,8 Likewise, 59% of HIV-infected adults with CD4 counts >500 cells/mm 3 responded to the H1N1 vaccine, vs. 80% of uninfected adults. 5 A significantly decreased vaccine response in adults with well-controlled HIV infection has also been demonstrated for the pneumococcal conjugate vaccine 6 and the HBV vaccine series. 4 Chronic infections with viruses such as cytomegalovirus (CMV), HBV, and hepatitis C virus (HCV) have been linked to immune dysfunction and decreased vaccine response in the general population.…”
Section: Introductionmentioning
confidence: 89%
“…Although this improves with cART and CD4 count recovery, the vaccine response in HIV-infected adults with CD4 counts in the normal range remains lower than in uninfected individuals. [4][5][6] For example, 80% of HIV-infected adults with CD4 counts >500 cells/mm 3 achieved seroprotection against hepatitis A virus (HAV) after a 2-dose HAV vaccine series, versus >94% of the general population. 7,8 Likewise, 59% of HIV-infected adults with CD4 counts >500 cells/mm 3 responded to the H1N1 vaccine, vs. 80% of uninfected adults.…”
Section: Introductionmentioning
confidence: 99%